Analysis of the WiFi4EU initiative as a potential instrument to correct digital divide in rural areas in the EU - Julio Navío-Marco; Raquel Pérez-Leal; Luis Manuel Ruiz-Gómez (International Telecommunications Society (ITS), 2019)
With the WiFi4EU initiative, the European Commission intends to reinforce local wireless Internet connectivity free of charge and without discriminatory conditions in the EU. This paper aims to analyse if this policy measure achieves its goals: to contribute towards digital inclusion and to improve coverage in disadvantaged areas. By analysing the results of the first call, we can conclude that WiFi4EU can be a good tool for promoting the necessary connectivity in local/rural environments of the European Union, but there is room for improvement to increase the positive impact of the initiative. The article proposes useful recommendations for municipalities and policymakers, and suggests improvements for the award procedure.
Keywords: 330; WiFi4EU; ICT regulation; Gigabit Society; Rural connectivity; digital divide